THE EFFECT OF INTERNAL COST MANAGEMENT, INTEGRATION OF EXTERNAL AND INTERNAL INFORMATION SYSTEMS, AND FIBER CAPACITY ON INTER-ORGANIZATIONAL COST MANAGEMENT IN SUPPLY CHAINS (Empirical Studies in Manufacturing Companies in The Province of Banten) - Gunawan, Gugun (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
Inter-organizational cost management is a strategic cost management approach to managing costs that span organizational boundaries in supply chains. Drawing on the resourcebased view of the firm, we develop a model to predict which inter-related resources might enable companies to manage inter-organizational costs. We test this model using a survey of managerial accountants whose organizations are part of a supply chain. Using structural equation modeling, we conclude that the resources of internal electronic integration, external electronic integration, internal cost management, and absorptive capacity play significant direct and indirect roles in the development of an inter-organizational cost management (IOCM) resource. We find that these resources are inter-related and together are useful in enabling companies to ultimately benefit from managing inter-organizational costs. We find in particular the importance of relational resources associated with absorptive capacity in the development of an IOCM resource. Our research contributes to theory and practice by explaining how specific resources can be combined in allowing companies to better manage inter-organizational costs. Data were analyzed using SEM with the aid SmartPLS software version 3.0